TRADISI MANDI BALIMAU DI MASYARAKAT KUNTU: Living Hadis Sebagai Bukti Sejarah - Dona Kahfi. MA. Iballa (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
Living Hadis is respons of certain community of muslims which is based by a “hadis” itself. It is containing in personal or also in community life in human society. Living hadis is an acculturation or assimilation between Islam’s doctrine and some of local’s cultures. Acculturation and assimilation between them produces a tradition which is known as living tradition or if it is based on thought that the foundation of the tradition is Hadith, it is called by living hadis. One of a phenomenon of living hadis which is exists in Kuntu society is tradition of Mandi Balimau. It is can be understood as living hadis by two indications. First, its basic is to missionize doctrine of Islam’s missionary endeavor. Second, it is to put into practice a sacred text which is known by Kuntu society by hadis. Mandi Balimau as one of phenomenon of living hadis could be proof of history of first Islamization in Nusantara especially in Riau. It manifested that Kuntu is one of the first regions in Nusantara that Islam introduced with and it also proofed that process of islamization in Nusantara occurred tranquility.